Short term effect of oxygen on renal haemodynamics in patients with hypoxaemic chronic obstructive airways disease. Issue 7 (July 1992) - Baudouin, S V; Bott, J; Ward, A; Deane, C; Moxham, J
Abstract : BACKGROUND: Oxygen therapy is effective in the prevention and treatment of oedematous exacerbations of cor pulmonale. As renal blood flow is reduced in cor pulmonale a study was designed to investigate whether one of the beneficial effects of oxygen was to increase renal blood flow. The effect of oxygen therapy on renal haemodynamics measured noninvasively was examined in patients with chronic obstructive airways disease and previous episodes of oedema. METHODS: Renal blood flow waveforms were recorded in a single vessel by colour flow Doppler ultrasound in nine hypoxaemic patients (PaO2) (arterial oxygen tension < 8 kPa while they were breathing air) with chronic obstructive airways disease and previous oedema and eight age matched normoxaemic volunteers (arterial oxygen saturation (SaO2) 97% or more when breathing air) while they were breathing air and oxygen. SaO2 and transcutaneous PaO2 (TcPO2) and PaCO2 (TcPCO2) were monitored. Five renal velocity profile recordings were made from the same segmental vessel with the patient breathing room air for one hour followed by oxygen titrated to achieve an oxygen saturation of 95% or more without a rise in TcPCO2 for 15 minutes. Control subjects breathed 35% oxygen. RESULTS: No significant change in the pulsatility index (a measure of distal vascular resistance) or mean height of the waveform (Tamx, a measure of renal blood flow) occurred in the control subjects while they were breathing air or oxygen. The pulsatility index of the patients with chronic obstructive airways disease was significantly greater than that in the control subjects breathing air (1.44 (SD 0.28) v 1.03 (0.14). Breathing oxygen was associated with an increase in TcPO2 in the patients (from 6.9 (1.9) to 11.5 (0.7) kPa), a fall in pulsatility index (from 1.44 (0.28) to 1.26 (0.14) and an increase in Tamx (from 0.187 (0.055) to 0.234 (0.087) m/s). CONCLUSIONS: The results suggest that renal vascular resistance is increased in patients with chronic obstructive airways disease and hypoxaemia and that short term oxygen therapy reduces renal vascular resistance and increases blood flow. Some of the benefits of oxygen therapy in cor pulmonale may be due to improvements in renal haemodynamics.